APPLICATION OF HIGH ALLOY CAST STEEL MATERIAL ON THE GRINDING COMPONENT (HAMMER) IN HAMMER MILL MACHINE - Fajar Nurjaman; Slamet Sumardi; Anton Sapto Handoko (Pusbindiklat - LIPI, 2011)
Hammer mill is one kind of machine that needs high durability, especially for grinding components such as hammers, which has a function to crush stone (mineral) in to ﬁ nely shaped (mesh 80). So these components should be made from materials which have some properties, such as high strength, toughness, and wear resistance. In his experiment, the hammers was made from high alloy cast steel, by using mangan, chrom, and copper as alloying materials. The chemical composition of these hammers are: (1) 3 5% Mn – 3 5% Cr – 3 5% Cu; (2) 4 6% Mn – 3 5% Cr – 7 9% Cu; (3) 3 5% Mn – 4 6% Cr – 7 9% Cu; (4) 3 5% Mn – 3 5% Cr – 10 12% Cu; (5) 5 7% Mn – 4 6% Cr – 14 16% Cu. Some of mechanical testing was given to these hammers, such as hardness testing, microstructure analysis testing, and also durability evaluation by using hammer mill machine with capacity 300 kg iron ore/hour. From durability evaluation, those hammers which are made from high alloy cast steel, with mangan, chrom, and copper as alloying material, showed a good result in wear rates by less than 0.4 mm2/kg iron ore. The lowest wear rates of this hammers is 0.14 mm2/kg iron ore, showed by hammers which had a composition 1.6%C – 3.2%Mn – 4.5% Cr – 3.2%Cu with 360 HBN in hardness value.